Resource utilization of electroplating wastewater: obstacles and solutions. Issue 3 (27th January 2022) - Li, Shuai; Dai, Min; Wu, Yanni; Fu, He; Hou, Xiaoting; Peng, Changsheng; Luo, Huihong
Abstract : The source, composition and impacts of impurities on electroplating wastewater treatment are discussed to achieve higher recovery of metals and water. Abstract : Industrial development has led to the discharge of large amounts of electroplating wastewater. The effective treatment of electroplating wastewater is of great significance. And the recovery of metals and water from electroplating wastewater should be the ultimate goal in the treatment. Many advanced technologies have been proven to have good effects on electroplating wastewater treatment in the laboratory with simulated wastewater as the research object. However, practical application results showed that the efficiency of advanced technology was far lower than the theoretical value due to the various additives from the electroplating process. This phenomenon is worthy of attention. In this review, deficiencies and feasible solutions in the resource utilization of electroplating wastewater are re-examined from the perspective of the pretreatment. The sources and composition of the additives in electroplating wastewater and their effects on various treatment technologies are introduced. The removal methods of these impurities in electroplating wastewater were reviewed. And the removal methods that can be combined with resource utilization technology are summarized. The combination is promising in water reuse and heavy metal recovery in practical electroplating wastewater treatment.